Translational regulation by miR-301b upregulates AMP deaminase in diabetic hearts. (June 2018) - Tatekoshi, Yuki; Tanno, Masaya; Kouzu, Hidemichi; Abe, Koki; Miki, Takayuki; Kuno, Atsushi; Yano, Toshiyuki; Ishikawa, Satoko; Ohwada, Wataru; Sato, Tatsuya; Niinuma, Takeshi; Suzuki, Hiromu; et al.
Abstract: AMP deaminase (AMPD) plays a crucial role in adenine nucleotide metabolism. Recently we found that upregulated AMPD activity is associated with ATP depletion and contractile dysfunction under the condition of pressure overloading in the heart of a rat model of type 2 diabetes mellitus (T2DM), OLETF. Here we examined the mechanism of AMPD upregulation by T2DM. The protein level of 90-kDa full-length AMPD3 was increased in whole myocardial lysates by 55% in OLETF compared to those in LETO, a non-diabetic control. In contrast, the mRNA levels of AMPD3 in the myocardium were similar in OLETF and LETO. AMPD3 was comparably ubiquitinated in OLETF and LETO, and its degradation ex vivo was more sensitive to MG-132, a proteasome inhibitor, in OLETF than in LETO. MicroRNA array analysis revealed downregulation (>50%) of 57 microRNAs in OLETF compared to those in LETO, among which miR-301b was predicted to interact with the 3'UTR of AMPD3 mRNA. AMPD3 protein level was significantly increased by a miR-301b inhibitor and was decreased by a miR-301b mimetic in H9c2 cells. A luciferase reporter assay confirmed binding of miR-301b to the 3′UTR of AMPD3 mRNA. Transfection of neonatal rat cardiomyocytes with a miR-301b inhibitor increased 90-kDa AMPD3 and reduced ATP level. The results indicate that translational regulation by miR-301b mediates upregulated expression of cardiac AMPD3 protein in OLETF, which potentially reduces the adenine nucleotide pool at the time of increased work load. The miR-301b-AMPD3 axis may be a novel therapeutic target for intervening enegy metabolism in diabetic hearts. Highlights: Upregulated myocardial AMPD activity was associated with ventricular dysfunction by diabetes. Protein level of full-length AMPD3 was two-fold higher in diabetic heart. AMPD3 mRNA level was unchanged but 57 microRNAs were downregulated in diabetic heart. Of the 57 miroRNAs, miR-301b targeted AMPD3 mRNA and reduced AMPD3 protein. Translational regulation by miR301-1b mediates diabetes-induced AMPD3 upregulation.